Treffinger Learning Model in Teaching Speaking - Akbarani, Rizqi (Academic Journal PERSPECTIVE: Education, Language, and Literature, 2019)
This research aims to find out how was the implementation of Treffinger learning model in teaching speaking skill. This research was applied for the tenth grade students of SMK Negeri 2 Madiun that consist of 26 students as sample in conducting the research. In collecting the data, research used observation to observe the implementation of Treffinger learning model during teaching learning process and used test to find the improvement of students’ speaking skill during implementation of Treffinger learning model.  The research finding showed that the implementation of Treffinger learning model can improve the students’ speaking skill. It can be concluded that Treffinger learning model is acceptable to be used as teaching learning model in teaching speaking.